Synthesis and structural characterization of bis(2-amino-1,3,4- thiadiazolyl)methane complexes - Adiguzel, Ragip; Ergin, Zuhal; Sekerci, Memet; Tascioglu, Senay (My University, 2011)
In this study, some transition metal complexes of the bis(2-amino-1,3,4- thiadiazolyl)methane (L) derived from the condensation of malonic acid and thiosemicarbazide, have been synthesized and characterized by IR, 1H-NMR spectra, elemental analyses, magnetic susceptibility and thermogravimetry-differential thermal analysis (TGA-DTA). Coordination numbers of monomeric, Ni(II), Zn(II), and Cd(II) complexes and dimeric Cu(II) complex were found to be four, five, six, and five, respectively. According to the elemental analyses and mass spectra data, the following complex formulas were proposed;[Ni2(L)(SO4)2(H2O) 2].CH3OH.0.5H2O, [Cu(L)(SO4)(H 2O)]2DMF.3H2O, [Zn(L)NO3.H2O]. NO3.DMF, and [Cd(L)2(NO3)H2O]NO 3.DMF. Ni(II) and Cu(II) complexes were paramagnetic. Ni(II), Cu(II), and Cd(II) complexes were proposedto be tetrahedral/square planar, square pyramidal, and octahedral structure, respectively. Zn(II) complex is five coordinated. The molar conductance data revealed that Zn((II), and Cd(II) complexes were 1:1 electrolytes(ionic). Ni(II), and Cu(II) complexes were non-electrolytes.